2013
DOI: 10.1002/smj.2087
|View full text |Cite
|
Sign up to set email alerts
|

Multinationality and downside risk: The roles of option portfolio and organization

Abstract: Multinational operations confer firms a portfolio of switching options that offer potential operating flexibility in the context of input cost variability, helping firms reduce downside risk. We suggest that two conditions may shape the relationship between multinationality and downside risk. When subadditivity is present in a firm's option portfolio, such as when the firm operates affiliates in host countries with similar labor cost developments, multinationality is less likely to reduce downside risk since l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 75 publications
4
106
2
Order By: Relevance
“…Our theoretical arguments in support of this finding suggest that subsidiaries with diverse investment purposes can benefit from enhanced abilities of adaptability and learning, which are crucial when operating in such dynamic and institutionally less developed locations (Jackson, ; Teece et al ., ). Subsidiaries with less diverse purposes are more susceptible to adverse changes in the environment (Belderbos et al ., ), limiting their ability to redirect focus and remain in operation. However, for subsidiaries with more diverse purposes, it is less likely that an environmental change that affects one of the purposes will also affect the other; hence, in such a situation, these subsidiaries can remain viable by redeploying more of their resources and attention to the purpose that is not adversely hit by the change.…”
Section: Discussionmentioning
confidence: 97%
“…Our theoretical arguments in support of this finding suggest that subsidiaries with diverse investment purposes can benefit from enhanced abilities of adaptability and learning, which are crucial when operating in such dynamic and institutionally less developed locations (Jackson, ; Teece et al ., ). Subsidiaries with less diverse purposes are more susceptible to adverse changes in the environment (Belderbos et al ., ), limiting their ability to redirect focus and remain in operation. However, for subsidiaries with more diverse purposes, it is less likely that an environmental change that affects one of the purposes will also affect the other; hence, in such a situation, these subsidiaries can remain viable by redeploying more of their resources and attention to the purpose that is not adversely hit by the change.…”
Section: Discussionmentioning
confidence: 97%
“…Fifth, prior research suggests that greenfield ventures and acquisitions may confer different option values (e.g., Brouthers & Dikova, 2010;Smit & Kil, 2017), so we include the variable Acquisition Ratio, measured as the percentage of entries through acquisition in a firm's foreign affiliates. Finally, we control for the value of switching options available from the firm's network of multinational operations (Chang, Kogut, & Yang, 2016;Fisch & Zschoche, 2012;Kogut & Kulatilaka, 1994a;Tong & Reuer, 2007b) by including the variable Switching Flexibility, calculated as one minus the correlation in labor cost across all host countries (e.g., Belderbos, Tong, & Wu, 2014).…”
Section: Control Variablesmentioning
confidence: 99%
“…Trigeorgis () showed that when real options involve redundancy (e.g., put‐type options such as to contract, switch use, or abandon all paying off in adverse conditions), they may be worth much less than the sum of separate values. In the strategic management literature, Vassolo, Anand, and Folta () examined this idea in the context of biotech alliances, while Belderbos, Tong, and Wu () examined it in the context of multinational investment. Makadok () studied the interaction effects of rivalry restraint and competitive advantage on firm profits and found a strong negative interaction due to a plausible inconsistency to pursue both of these pathways to profit concurrently.…”
Section: Literature and Information Structurementioning
confidence: 99%